Relationship between area and wind speed along the edge of the Antarctic polar vortex - V. V. Zuev; E. S. Savelieva; В. В. Зуев; Е. С. Савельева (Arctic and Antarctic Research, 2022)
The Antarctic polar vortex forms in autumn, intensifies in the winter-spring period and decays in late spring. Inside the vortex in the lower stratosphere, favorable conditions are created for the annual spring ozone depletion. One of the conditions for the formation of the Antarctic ozone hole is the presence of a dynamic barrier along the vortex edge in the winter-spring period, which contributes to a decrease in temperature inside the vortex (necessary for the existence of polar stratospheric clouds) and prevents the penetration of air masses into the vortex. The dynamic barrier exists when the wind speed along the vortex edge in the lower stratosphere is at least 20 m/s. When the vortex area decreases below 10 million km2 , the dynamic barrier usually weakens, preceded by the vortex breakdown. The purpose of this work is to consider the relationship between the vortex area and the wind speed along the vortex edge using the Antarctic polar vortex as an example. To analyze the dynamics of the Antarctic polar vortex, we used a method based on vortex delineation, which makes it possible to calculate the vortex area and wind speed along the vortex edge using geopotential values determined from the maximum values of temperature gradient and wind speed and, thus, characterizing the polar vortex edges. Seasonal variations in the vortex area are mainly determined by the time of the beginning, peak and end of the polar night. In turn, seasonal changes in wind speed along the edge of the Antarctic vortex are additionally determined by the influence of the temperature of the lower subtropical stratosphere. To eliminate the influence of the seasonal variation, polynomial trends were removed from the time series of the parameters considered. We have shown that the relationship between the vortex area and the wind speed along the vortex edge can be traced for area values of less than 25 million km2 and more than 50 million km2 . At small values of the vortex area (< 25 million km2), during its formation and destruction, ...